Bilateral Phacoemulsification in an African Elephant (Loxodonta africana). (10th July 2019) - Cerreta, Anthony J.; McMullen Jr, Richard J.; Scott, Heather E.; Ringenberg, Jennifer D.; Hempstead, Julie E.; DeVoe, Ryan S.; Loomis, Michael R.; Minter, Larry J.
Abstract : A 37-year-old bull African elephant ( Loxodonta africana ) at the North Carolina Zoo (NCZ) was diagnosed with bilateral cataracts leading to behavioral changes and significant weight loss secondary to functional blindness. On initial examination, a weight loss of 234 kg, a mature cataract in the right eye, and a focal cataract in the left eye were diagnosed. Ultrasound and electroretinography (ERG) indicated normal retinal attachment and both eyes were viable candidates for surgery. After careful planning and behavioral training, the left cataract was surgically removed via phacoemulsification and irrigation/aspiration. The right eye subsequently developed a ventral lens subluxation, and phacoemulsification and irrigation/aspiration were performed six months after the first procedure. Four years after surgery, menace response, palpebral reflex, dazzle reflex, and pupillary light reflexes were present in both eyes. Body weight was 5, 515 kg, 88kg more than at the time of the second surgery. This is the first published report of an African bull elephant undergoing bilateral cataract removal using phacoemulsification and irrigation/aspiration. The lack of significant postoperative inflammation and uneventful recovery of the elephant suggests that this surgical procedure along with proper preoperative planning and postoperative medical management can be a safe and effective treatment option for elephants with cataracts.